Transmedialne losy wybranych fragmentów XVI- i XVII-wiecznej poezji i prozy Johna Donne’a jako ilustracja społecznej użyteczności śmiechu - Gładkowska, Dorota (Acta Neophilologica, 2020)
This article indicates the specific manner in which early modern literature is exploited in contemporary media. It focuses on the interaction involving the trans-position of philosophical texts to the domain of laughter embedded in the everyday life of the modern recipient. Selected passages of John Donne’s (1572-1631) prose and poetry serve to illustrate how an old literary work encourages new creativity, how it transcends the boundaries set by a given epoch, culture and form, to undergo a specific thematic and structural transformation. What seems particularly interesting in this process is the conversion of philosophical sadness into a useful joke incorporated in, inter alia, the transition from meditation to motivation, from inspiration to action. In other words, this article examines laughter provoked at the interface between a profound philo-sophical message and popular entertainment which combines images and words and activates the intellect as well as the senses and emotions. Such foundations give rise to a transmedia message being socially functional – not only as comic relief, but also as a didactic tool for shaping attitudes.